Challenges and the Way Forward for Management and Handling of Hazardous Waste - Jena, Madhab C.; Mishra, Sarat K.; Moharana, Himanshu S. (The Global Environmental Engineers, 2023)
Hazardous waste poses significant threats to human health and the environment, necessitating stringent regulatory management. This study explores the challenges and prospects associated with hazardous waste management, emphasizing the critical need for sustainable practices. Drawing on field observations, stakeholder interviews in India, and extensive literature reviews, the research addresses challenges such as inadequate stakeholder consultation during law enactment, resource constraints, insufficient authorized disposal facilities, and transportation issues. The study underscores the importance of sustainable waste reduction practices through proactive industry engagement and government facilitation of necessary infrastructure. It advocates for streamlined regulatory processes, inter-state cooperation, and responsive authorities to ensure effective hazardous waste management. The research emphasizes the adoption of innovative and sustainable waste reduction methods supported by comprehensive root cause analysis and well-crafted policies to achieve environmental sustainability goals. In conclusion, the study highlights the global applicability of findings, emphasizing collaborative efforts for effective hazardous waste handling and disposal to ensure a clean and pollution-free environment.